The Effects of Contracting, Litigation, Regulation, and Tax Costs on Conditional and Unconditional Conservatism: Cross-Sectional Evidence at the Firm Level - Qiang, Xinrong (The Accounting Review, 2007)
Prior studies propose four explanations for accounting conservatism, and recent studies classify conservatism into two forms: conditional and unconditional conservatism. This paper examines whether each proposed explanation applies to conditional conservatism, unconditional conservatism, or both. The findings are as follows: (1) contracting induces conditional conservatism; (2) litigation induces both forms; (3) regulation induces unconditional conservatism; and (4) taxation induces unconditional conservatism. These findings indicate that the two forms of conservatism play distinct roles in contracting, regulation, and taxation, as well as a common role in litigation. They also play an interrelated role, as suggested by the finding that unconditional conservatism reduces conditional conservatism. The combined evidence implies that because the two forms meet distinct needs but are negatively interrelated, it is necessary to trade them off.